Preservation of Gamelan Melayu recordings through sound engineering - Munusamy, Muralitheran (2020)
Sound or audio engineering is a branch of the engineering field which involves the process of recording sound and reproducing it by various means, as well as storing it so that it can be reproduced later. Known as sound or audio engineers, these trained professionals work in a variety of sound production fields and expert in recording methods. They can be instrumental to implement the affordable technologies and technical process to distribute the audio data so it will accessible to future generation. The current role of these engineers not only to perform or limited to recording session but they create metadata for archiving and preservation for future needs. Currently, product sleeves of ethnography recordings represent no technical elements of how traditional music recordings are produced. The product details focus only to some extent on historical elements and musical notation. To an audio archivist, declaring what devices are in a recording is unconnected for preservation data. Apart from the format, the sleeved design, technical specification is essential to other social scientists such as audio engineer and field recordist of the future. Qualitative methods were used to study and implemented in this research to gain the data collection, the variables were measured on nominal scale, enables classification of individuals, objects or response based on a common and shared property of characteristic that represent the topic of the research project. The aim of the research is to capture optimum dynamic range of the sound that would not alter the tonality, timbre and harmonic of the sound and further applying a suitable information storage for the metadata to be preserve or archived for future accessing and reproduction. The findings of the research are used as informative and guideline for the target sample in current and future works in the field or industry they engage respectively.